2011
DOI: 10.3141/2210-09
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Deformation Model Based on Shear Properties of Asphalt Mixtures

Abstract: A permanent deformation model of asphalt concrete based on shear properties is developed and calibrated. This model is extended and improved from previous work with the use of laboratory test results. Triaxial compressive strength and repeated-load permanent deformation (RLPD) tests on three types of asphalt mixtures are performed at various loads and temperatures to correlate the shear properties of asphalt mixtures with rutting performance. Test results indicate that the cohesion and friction angle of a give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The shear strain from simple shear tests is also used to model permanent deformation [ 16 , 34 ]. The coupling of shear and axial strain components in permanent deformation modeling has not been performed yet in previous studies [ 35 ]. The indirect tensile test is also used for permanent deformation with different specimen dimensions of 150 or 100 mm diameter by 50 to 70 mm thickness [ 36 ].…”
Section: Permanent Deformation Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shear strain from simple shear tests is also used to model permanent deformation [ 16 , 34 ]. The coupling of shear and axial strain components in permanent deformation modeling has not been performed yet in previous studies [ 35 ]. The indirect tensile test is also used for permanent deformation with different specimen dimensions of 150 or 100 mm diameter by 50 to 70 mm thickness [ 36 ].…”
Section: Permanent Deformation Predictionmentioning
confidence: 99%
“…The computational modeling of asphalt concrete poses difficulties mainly due to the material nonlinearity, complexity to characterize under repeated and moving loads, and variable environmental conditions (temperature, moisture, etc.) [ 35 , 54 ]. The constitutive equations for the linear viscoelastic strain ( ) in undamaged conditions is defined by the Boltzmann superposition principle.…”
Section: Permanent Deformation Damage Modelingmentioning
confidence: 99%
“…The second empirical equation (Eq. 5) is proposed by the authors based on the results from a variety of tests (Fwa et al 2004;Wang et al 2008;Li et al 2011;Kim et al 2017) as shown in Figure 14. By using Eq.…”
Section: A Temperature-dependent Shakedown Approachmentioning
confidence: 99%
“…Several mechanistic or mechanistic-empirical models have been developed using the APT method. Monismith, Popescu, and Harvey (2006) and Li, Lee, and Lee (2011) developed a relationship between rutting and mixture shear properties obtained from triaxial compressive strength and repeated load permanent deformation tests. Park, Martin, and Masad (2004) developed an elasto-viscoplastic model based on Perzyna's viscoplastic theory and the Druker-Prager yield function to predict rutting measured in APTs.…”
Section: Accelerated Pavement Testing Techniquesmentioning
confidence: 99%